Interferon regulatory factor-3-mediated activation of the interferon-sensitive response element by Toll-like receptor (TLR) 4 but not TLR3 requires the p65 subunit of NF-kappa - O'NEILL, LUKE ANTHONY JOHN (The American Society for Biochemistry and Molecular Biology, 2003)
Interferon regulatory factor (IRF) 3 is a transcription factor that binds the interferon-sensitive response element (ISRE) and is activated by Toll-like receptor 3 (TLR3) and TLR4. We have found that a dominant negative form of I?B kinase 2 and a mutant form of I?B, which acts as a super-repressor of NF-?B, blocked activation of the ISRE by the TLR4 ligand lipopolysaccharide but not the TLR3 ligand poly(I-C). TLR4 failed to activate the ISRE in mouse embryonic fibroblasts bearing a targeted deletion of p65, whereas the response to TLR3 in these cells was normal. The p65 subunit of NF-?B was detected in the lipopolysaccharide-activated but not poly(I-C)-activated ISRE-binding complex. Finally, p65 promoted transactivation of gene expression by IRF-3. These results therefore indicate that IRF-3-mediated activation of the ISRE by TLR4 but not TLR3 requires the p65 subunit of NF-?B.
PUBLISHED
Keywords: Biochemistry